Isolation of Chitinase CDNAs and their Expressions in Oil Palm Elaeis Quineesis Jacq. Seedlings in Interaction with Ganoderma Boninense Pat. and Trichoderma - Naher, Laila (2011)
Basal stem rot (BSR), which is caused by the fungus Ganoderma boninense, is a serious disease that affects the oil palm (Elaeis guineensis), and it is a major threat to the oil palm industry. The disease escapes early detection. When fruiting bodies are detected the disease is too advanced to respond to any chemical treatments. Another fungus, Trichoderma harzianum has been proven to have high efficacy in controlling Ganoderma infection in oil palms only at early stage of infection of slightly infected palms. Therefore, to date there is no adequate control measure to control this disease. So, as a long term control measure, improvement of the oil palm defence system against G. boninense is the alternative option. The pathogenesis-related (PR) protein of plant chitinases belongs to the repertoire of plant defense mechanisms that are believed to constitute the early defense response in plants. Thus, the plant chitinases may be involved in the oil palm’s reaction to infection by G.boninense. The goal of this study was to investigate the potential role of chitinase mRNA’s expression and enzyme activity in oil palms infected by G. boninense strain PER71 as well as in samples treated with T. harzianum strain FA1132, which is a biocontrol agent used to combat BSR disease. The effectiveness of T. harzianum as a biocontrol agent for BSR disease and as a potential enhancer of plant growth as well as defence response in plants was also investigated. The disease severity index value (DSI) showed that G. boninense infected the oil palm root as early as at week 5 with DSI = 8.3% whereas physical symptoms appeared in leaves at week 8 with DSI =11.11%. In contrast, no disease symptoms were observed in plants treated with T. harzianum, either alone or in combination with G. boninense, and root and leaf weights markedly increased in these treatments. Although the chlorophyll concentration was not increased in T. harzianum treated plants but after 2 weeks post inoculation it was higher than in control plants and plants treated with only Ganoderma. Three chitinase classes were selected for cDNA isolation and characterization: EgCHI1, EgCHI2, and EgCHI3 were cloned and sequenced, and their expression patterns were analyzed. Nucleotide data indicated that the EgCHI1 and EgCHI2 sequences belong to glycoside hydrolase family 19, which contains chitinase classes I, II, and IV, and the EgCHI3 sequence belongs to glycoside hydrolase family 18, which consists of chitinase classes III and V. BLAST analysis revealed that EgCHI1 was highly similar (78%) to a class I chitinase from Arabidopsis thaliana (AAF29391.1); EgCHI2 was highly similar (78%) to a class II chitinase from Fragaria X Ananassa (AAF00131.1); and EgCHI3 was highly similar (72%) to a class III chitinase from Bambusa oldham (ABW75909.1). Expressions of these three cDNAs were observed in oil palm seedlings treated with G. boninense or T.harzianum either alone or together at time points of 2, 5, and 8 weeks post inoculation (wpi), respectively. For seedlings treated with G. boninense alone, the transcripts levels of all three chitinases in roots tissues were highest at 5 weeks post inoculation when the infection was visible, whereas chitinase enzyme activity was highest at 2 weeks post inoculation. At 8 weeks post inoculation when G. boninense infection was established, the chitinase expression was decreased but the chitinase enzyme activity slightly increased. The cDNAs expression data also revealed that the chitinases were constitutively expressed in root tissues but not in leaf tissues. Moreover, cDNA expression and the activity of enzyme were higher in root tissues compared to leaf tissues. EgCHI1 expression was up-regulated until 8 weeks post inoculation in roots and leaves of oil palms treated with a combination of G. boninense and T. harzianum. In conclusion, this study found that all three chitinases were expressed in the presence of G. boninense or T. harzianum but that the timing of chitinase expression varied depending on the type of treatment.